PROBLEM OF TREATMENT OF PATIENTS WITH HYPOSPADIAS (literature review) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Hypospadias -malformation of the penis of boys, in which there is a curvature of the penis towards the scrotum as a result of underdevelopment of the spongy part of the urethra. The external opening is located on the lower surface of the glans penis, scrotum or perineum of boys. The penis is deformed and bent downwards. Hypospadias develops as a result of a violation of embryogenesis at 7-14 weeks of intrauterine development of the fetus. Severe forms of hypospadias can be combined with impaired development of the internal genital organs. There are 3 main forms of hypospadias, capitate, stem, scrotum. In about 45% of cases, it is combined with other anomalies, among which the first place is occupied by cryptorchidism, meatostenosis, and inguinal hernia. According to Yu, F. Isakov hypospadias is the most common anomaly of the urethra and occurs in 1 in 150 newborn boys.